1997
DOI: 10.1097/00004872-199715030-00004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alternative criteria for hypertension on estimates of prevalence and control

Abstract: Different criteria to define hypertension can have important effects on the estimates of prevalence and control. Authors need to be explicit concerning the criteria used. Readers should be aware of the risk of overinterpreting results based on criteria that do not reflect their objectives (e.g. using a single visit estimate to determine control of clinically relevant hypertension).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 10 publications
1
24
1
2
Order By: Relevance
“…Using a single visit estimate to determine control of clinically relevant HT might have led to overestimation of the prevalence of HT. 26 The use of aneroid sphygmomanometers for BP measurements can be another limitation of the study. However, because the accuracy of these sphygmomanometers has been checked by using a closed system designed according to the recommendations of the American Heart Association (AHA) and British Hypertension Society (BHS), they are likely to be reliable, their measurements reproducible within machine and comparable between machines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a single visit estimate to determine control of clinically relevant HT might have led to overestimation of the prevalence of HT. 26 The use of aneroid sphygmomanometers for BP measurements can be another limitation of the study. However, because the accuracy of these sphygmomanometers has been checked by using a closed system designed according to the recommendations of the American Heart Association (AHA) and British Hypertension Society (BHS), they are likely to be reliable, their measurements reproducible within machine and comparable between machines.…”
Section: Discussionmentioning
confidence: 99%
“…Because different criteria to define HT can have important effects on the estimates of prevalence and control 26 and for the purpose of comparison with other studies, we computed the estimates of prevalence of HT and its control using two different BP cut-off points: as recommended by the JNC V (140 and/or 90 mm Hg) and according to the WHO/ISH criteria mostly used in Europe (160 and/or 95 mm Hg). 1,4 Although few national or regional surveys have been undertaken on the epidemiology of HT in Turkey, the data from these studies indicate some similarities with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol was followed as previous studies on hypertension and the pilot survey in the rural area have shown that measuring BP pressure on different visits takes into account BP variability of the subjects. 12,13 Weight was recorded on a measuring scale (bathroom scale) using standard methods. The scale was calibrated after every 15 days with a standard beam scale.…”
Section: General Examinationmentioning
confidence: 99%
“…O uso de uma única medida para determinar a pressão arterial de um paciente resultaria em 20 a 30% de falsos positivos e 1/3 de falsos negativos (Reeves, 1995, Birkett, 1997.…”
Section: Definição E Importânciaunclassified